Minimally invasive versus open distal pancreatectomy for pancreatic ductal adenocarcinoma (DIPLOMA): study protocol for a randomized controlled trial - Hilst, Jony van; Hackert, Thilo (Trials, 2021)
Recently, the first randomized trials comparing minimally invasive distal pancreatectomy (MIDP) with open distal pancreatectomy (ODP) for non-malignant and malignant disease showed a 2-day reduction in time to functional recovery after MIDP. However, for pancreatic ductal adenocarcinoma (PDAC), concerns have been raised regarding the oncologic safety (i.e., radical resection, lymph node retrieval, and survival) of MIDP, as compared to ODP. Therefore, a randomized controlled trial comparing MIDP and ODP in PDAC regarding oncological safety is warranted. We hypothesize that the microscopically radical resection (R0) rate is non-inferior for MIDP, as compared to ODP.